Physicochemical and Thermal Characteristics of Onion Skin from Fifteen Indian Cultivars for Possible Food Applications - Narashans Alok Sagar; Anil Khar; Vikas; Ayon Tarafdar; Sunil Pareek (Journal of Food Quality)
Every year tons of onion waste is produced worldwide. The dried outer onion skin contributed up to 70% of this waste. Outer-dried skins of fifteen prominent onion cultivars from India were selected for the study. A comparative study was done for proximate profiling, thermal characteristics, functional grouping, and mineral contents. Skin of cv. “NHRDF Red” contained the highest amount of crude protein (5.97 ± 0.15 g/100 g), ash (12.24 ± 0.59 g/100 g), and fiber (8.28 ± 0.20 g/100 g), whereas cv. “Pusa Red” possessed the highest amount of total fat (0.47 ± 0.02 g/100 g) and the maximum carbohydrates (76.66 ± 0.56 g/100 g) were found in “Pusa Riddhi.” Mineral analysis showed that cv. “NHRDF Red” had the maximum concentration of all 9 minerals along with sulphur content. Fourier transform infrared spectroscopy analysis explored the various metabolites present in each cultivar. The thermal analysis explored cv. “Agrifound Dark Red” as highly thermally stable having 70.98% residual mass. The lowest Tg temperature range was found between 64.4°C and 90.6°C for “Agrifound Dark Red.” Skin of cv. “NHRDF Red” was reported as the best source of protein, fiber, and minerals, which may be utilized for developing a food product.